Edukasi "Self-Love to Increase Self-Confidence" : Upaya Membangun Rasa Percaya Diri dan Berhenti Membandingkan Diri dengan Orang Lain - Fuji Dwilestari; Siti Munawaroh; Hesti Fathan Nurfais Fauziah; Yayuk Fransiska Novitaningrum; Vina Nikmatul Husna; Naufal Dzikrun Najizin (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Mental health is an essential component of achieving overall well-being and optimal health. However, in many developing countries, mental health issues continue to receive relatively limited attention and are often not prioritized compared to the management of infectious diseases. In this context, many adolescent girls in Indonesia still do not fully understand the essence of self-love, which refers to the ability to appreciate, accept, and value oneself. Objective: This community service program aimed to enhance adolescents' knowledge and understanding of mental health and self-love through health education delivered using interactive learning media. Method: The educational intervention was conducted through lectures, group discussions, and question-and-answer sessions. The community service activity was carried out on Tuesday, May 19, 2026, at SMP Muhammadiyah 6 Kendal and involved 17 students, consisting of 10 male students and 7 female students. All participants who attended the program were included as the study sample. Result: The results showed an increase in knowledge among all participants after receiving health education on mental health and self-love. The pre-test scores reflected the participants' level of knowledge before the educational intervention, while the post-test scores indicated their level of knowledge after the intervention. Overall, the pre-test scores ranged from 40 to 75, with a mean score of 59.1, whereas the post-test scores increased to a range of 80 to 100, with a mean score of 91.4. Conclusion: The results showed an increase in participants' knowledge of mental health and self-love following the educational intervention. The “Self-Love in the Digital Era” program was designed as a preventive and educational effort to address mental health challenges by promoting self-acceptance and the wise use of social media, thereby fostering resilience and self-confidence among adolescents.